The Value Preferences in the Anasoft litera Award - Makara, Martin (Mundus Slavicus I, 2025)
The study deals with the laureates of the most prestigious Slovak literary award, Anasoft litera, and how the juries reasoned the winning titles throughout the years. Mapping up to two decades of the annual award, the paper focuses on values highlighted in the official rationale behind every year’s winner. This results in a diachronic panorama of Anasoft litera’s value preferences, capturing its development from the noticeable domination of aesthetic criteria at the beginning of the award to a more balanced approach with other types of criteria – mainly social – in the last years of the award.